2019
DOI: 10.1097/pgp.0000000000000657
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Immune Checkpoints LAG-3 and PD-L1 in High-grade Serous Ovarian Carcinoma: Relationship to Tumor-associated Lymphocytes and Germline BRCA Status

Abstract: Ovarian high-grade serous carcinomas (HGSC) have shown lackluster responses to immunotherapies targeting the PD-1/PD-L1 axis, perhaps due to the coexistence of other mechanisms of immune evasion in this tumor type. Lymphocyte activation gene-3 (LAG-3) is another inhibitory immune checkpoint often expressed on tumor-associated lymphocytes which is targeted by drugs currently in clinical trials. Forty-eight HGSC with known germline BRCA mutation status were immunohistochemically stained for LAG-3, CD8, and FOXP3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Many patients have no response to therapies that target CTLA‐4 and PD‐1 37 . Moreover, the lackluster response in clinic application of anti‐PD‐1 to HGSOC supports our result 38 . By genome‐wide gene expression correlation analysis, we found that PD‐1 expression was highly correlated with SIRPG, FASL, and CD8a.…”
Section: Discussionsupporting
confidence: 83%
“…Many patients have no response to therapies that target CTLA‐4 and PD‐1 37 . Moreover, the lackluster response in clinic application of anti‐PD‐1 to HGSOC supports our result 38 . By genome‐wide gene expression correlation analysis, we found that PD‐1 expression was highly correlated with SIRPG, FASL, and CD8a.…”
Section: Discussionsupporting
confidence: 83%
“…Like in breast cancer, there are also a few studies in ovarian cancer that do not support an association between BRCA -inactivation and immune cell infiltration. In an immunohistochemistry study including 48 patients with serous ovarian cancer and known germline BRCA mutation status (4 BRCA1 -mutated, 8 BRCA2 -mutated, 36 BRCA -wildtype), no association was found between germline BRCA mutation status and the infiltration of CD8 + T cells or Tregs or checkpoint expression (PD-L1 or LAG-3) [ 59 ]. Furthermore, analyses of transcriptome data of the TCGA yielded conflicting results [ 19 , 60 ].…”
Section: The Tumor Immune Microenvironment In Brca-inactivated Tumorsmentioning
confidence: 99%
“…BRCA1 regulates the cellular DNA damage response and repair, transcriptional regulation, and chromatin modeling, while BRCA2 plays a role in the DDR processes [ 9 , 19 , 23 , 53 , 56 , 92 , 163 ]. In PC, BRCA1 co-regulates the AR activity mediating tumor progression, while BRCA2 limits the metastatic potential of PC by MMP9 downregulation and inhibition of the PI3K/AKT and MAP/ERK pathways (which also regulate PD-L1 expression) [ 163 , 164 , 183 , 184 ].…”
Section: Discussionmentioning
confidence: 99%